2022
DOI: 10.1007/s12028-022-01613-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Invasive Brain Oxygen Pressure Guided Therapy on the Outcome of Patients with Traumatic Brain Injury: A Systematic Review and Meta-Analysis

Abstract: Traumatic brain injury (TBI) is a major public health burden, causing death and disability worldwide. Intracranial hypertension and brain hypoxia are the main mechanisms of secondary brain injury. As such, management strategies guided by intracranial pressure (ICP) and brain oxygen (PbtO 2 ) monitoring could improve the prognosis of these patients. Our objective was to summarize the current evidence regarding the impact of PbtO 2 -guided therapy on the outcome of patients with TBI. We performed a systematic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…However, the individualization of therapies based on the combination of ICP and PbtO 2 also necessitates clinical validation and have several limitations (see next paragraph ). A systematic review, primarily comprising 15 studies (involving a total of 37,245 patients), although predominantly observational with an overall low quality of evidence, indicated that the use of combined ICP/PbtO 2 -guided therapy, as opposed to ICP-guided therapy alone, was significantly associated with a higher likelihood of achieving a favorable neurological outcome and improved hospital survival [ 47 ]. In a phase II randomized trial conducted across 10 neuro-ICUs in the USA, a management protocol incorporating continuous PbtO 2 monitoring alongside ICP monitoring demonstrated a notable reduction in the duration of brain tissue hypoxia among severe TBI patients, in comparison with those monitored for ICP alone [ 48 ], with a nonsignificant improvement in the proportion of patients achieving a favorable neurological outcome at 6 months.…”
Section: The Fourth Domain: Focus On Brain Oxygenation and Metabolismmentioning
confidence: 99%
“…However, the individualization of therapies based on the combination of ICP and PbtO 2 also necessitates clinical validation and have several limitations (see next paragraph ). A systematic review, primarily comprising 15 studies (involving a total of 37,245 patients), although predominantly observational with an overall low quality of evidence, indicated that the use of combined ICP/PbtO 2 -guided therapy, as opposed to ICP-guided therapy alone, was significantly associated with a higher likelihood of achieving a favorable neurological outcome and improved hospital survival [ 47 ]. In a phase II randomized trial conducted across 10 neuro-ICUs in the USA, a management protocol incorporating continuous PbtO 2 monitoring alongside ICP monitoring demonstrated a notable reduction in the duration of brain tissue hypoxia among severe TBI patients, in comparison with those monitored for ICP alone [ 48 ], with a nonsignificant improvement in the proportion of patients achieving a favorable neurological outcome at 6 months.…”
Section: The Fourth Domain: Focus On Brain Oxygenation and Metabolismmentioning
confidence: 99%
“…The rate of mortality in the PbtO 2 monitoring group was 29.0% across all studies included in our analysis, which is different from the previously reported rate based on a meta-analysis by Xie [ 4 ]. Studies have demonstrated that brain hypoxia is associated with poor prognosis after TBI and optimizing PbtO 2 can improve recovery and survival rates [ 26 ]. Four observational studies [ 19 , 20 , 22 , 23 ] and two randomized controlled trials [ 16 , 25 ] included in this meta-analysis demonstrated that when PbtO 2 was incorporated into clinical management decisions, neural function exhibits statistically significant benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Early interventions after acute traumatic brain injury (TBI) provide clinicians an opportunity to prevent secondary injury and improve neurologic outcomes. One avenue is to optimize brain tissue oxygenation (Pbt o 2 ) (1). Many variables impact cerebral blood flow (CBF) and subsequent brain tissue oxygen delivery and extraction, including systemic blood pressure, arterial blood oxygen and C o 2 levels, serum pH, hemoglobin, microvascular shunts, and metabolic demands (2, 3).…”
mentioning
confidence: 99%
“…CBF can be assessed directly at the bedside using transcranial Doppler (TCD) ultrasound monitoring. Alternatively, the pressure reactivity index is calculated as a dynamic correlation coefficient between ICP and mean arterial pressure (MAP), which can be plotted against CPP to produce patient-specific optimal autoregulatory capacity (CPP opt ) (1). Both TQIP and SIBCIC recommend performing a MAP challenge to assess the autoregulatory capacity of CBF.…”
mentioning
confidence: 99%
See 1 more Smart Citation